The Syriac Reception of John Chrysostom’s Homilies against the Jews: First Soundings - Minov, Sergey (Zeitschrift für antikes Christentum, 2025)
This article presents previously unpublished fragments of the lost Syriac version of the Homilies against the Jews by John Chrysostom. The three excerpts, preserved in West Syrian collections of patristic texts, bear an important witness to the textual tradition of the Homilies and shed light on the dynamics of reception and transmission of the Greek Adversus Judaeos compositions among Syriac Christians during the early Islamic period. The texts are accompanied with an English translation and discussion.